(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Gender, location, and religious diversity are the main topics of this research, which examines the connection between social values and learning practices among secondary school pupils in Satna District. 770 peoples from both rural and urban locations had their data examined using a stratified random sample technique. Aspects like responsibility, equality, service, peace, tolerance, and environmental care were all assessed in the survey. In everything save environmental concern, where no discernible difference was seen, female students had higher mean scores. In service and equality, rural students outperformed their urban counterparts, but there were no discernible differences in other areas. Though not much in other areas, religious membership had an impact on how people saw equality. In order to promote holistic development, our results underscore the need of context-sensitive educational interventions by highlighting the complex interactions between demographic determinants and value formation.